Sulfuric acid, base, and low-volatility organics contribute to aerosol nucleation in urban Houston - Lee Tiszenkel; James H. Flynn; Alana Dodero; Shan-Hu Lee (Communications Earth & Environment)
Abstract Atmospheric aerosol nucleation is an extremely complex chemical process that produces aerosols directly from gas phase species, impacting air quality, human health, and climate. Current understanding of urban aerosol nucleation processes is based on the findings made mostly in Chinese mega-cities, but it is not clear the proposed sulfuric acid-amine nucleation process can be applied to all urban sites worldwide. Here, we conducted comprehensive measurements of nucleation precursors in Houston, the 4th most populated and polluted urban site in the United States. Our observations and box model simulations show that rapid aerosol nucleation and growth can be explained by the measured sulfuric acid, base, and low-volatility organics formed from oxidation of anthropogenic and biogenic volatile organic compounds. Given rapid global urbanization and increasing emissions of emerging chemical pollutants in the United States and Europe, this multicomponent nucleation process will be crucial for mitigating air pollution in the evolving urban climate.